How are countries responding differently to COVID-19: a systematic review of guidelines on isolation measures - Xie, Guangmei; Wang, Li; Zhang, Jun (Frontiers in Public Health, 2023)
Introduction Isolation strategies have been implemented in numerous countries worldwide during the ongoing community transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, various countries and organizations have implemented their isolation measures at varying intensities, even during the same period. Therefore, we systematically reviewed the key information contained in currently available guidelines regarding the isolation of the general population, aiming to better identify the heterogeneity of the current isolation strategies. Methods We conducted searches in four evidence-based medicine (EBM) databases and five guideline websites to identify guidelines, guidance, protocols, and policy documents published by authoritative advisory bodies or healthcare organizations, which provided information on the implementation of isolation for general populations with COVID-19. One author extracted data using a standardized data extraction checklist, and a second author double-checked all extractions for completeness and correctness. Discrepancies were resolved through discussion. The information extracted from the included articles was summarized both narratively and using tables. Results We included 15 articles that provided information on isolation measures recommended by nine different countries and organizations. The included articles consistently recommended isolating individuals with a positive COVID-19 test, regardless of the presence of symptoms. However, there were variations in the duration of isolation, and substantial differences also existed in the criteria for ending the isolation of COVID-19 patients. Conclusion Different countries and organizations have substantial differences in their isolation policies. This reminds us that scientifically sound guidelines on isolation that balance the risk of prematurely ending isolation with the burden of prolonged isolation are a crucial topic of discussion when faced with a pandemic.